English Reading Needs, Cultural Identity, and Technological readiness: A Need Analysis at an Indonesian State University - Eryansyah, Eryansyah -; Fiftinova, Fiftinova; Petrus, Ismail; Jaya, Hariswan Putera (Edukasi, 2026)
English reading proficiency is a fundamental requirement for university students in EFL contexts, yet reading instruction in Indonesian higher education often lacks alignment with students’ academic needs, cultural identity, and technological realities. This study aimed to investigate students’ needs in English reading instruction through a comprehensive needs analysis covering learning goals, current abilities, learning difficulties, perceptions of local wisdom integration, and technological readiness. A quantitative survey design was employed, involving 67 undergraduate students at a state university in South Sumatra. Data were collected through a structured needs analysis questionnaire and analysed descriptively using percentage distribution. The findings reveal that students perceive English reading as essential for future academic and professional purposes, with reading identified as the most relevant skill for anticipated language use. However, students report moderate current reading proficiency and significant vocabulary-related comprehension difficulties, indicating a clear gap between present ability and expected proficiency. The results further show strong student demand for English reading materials integrating South Sumatran local wisdom i.e., customs and arts, reflecting the importance of culturally responsive pedagogy in higher education EFL contexts. Additionally, while most students possess adequate digital devices, unstable internet connectivity and limited digital literacy present challenges for fully digital reading implementation. These findings suggest that effective English reading instruction in Indonesian universities should incorporate vocabulary-supported reading strategies, culturally contextualized materials, and technology-sensitive delivery. The study provides empirical evidence to support the development of needs-based and culturally responsive English reading curricula in higher education.